2006
DOI: 10.1534/genetics.106.057455
|View full text |Cite
|
Sign up to set email alerts
|

Complex Inheritance of the 5-Lipoxygenase Locus Influencing Atherosclerosis in Mice

Abstract: We previously mapped a locus on chromosome 6 with a large effect (LOD . 6) on aortic lesion size in a (C57BL/6J 3 CAST/Ei) F 2 cross and identified arachidonate 5-lipoxygenase (5LO) as a candidate gene in this region. Subsequent studies with the 5LO knockout model showed effects on atherosclerosis and aortic aneurysms. We now report detailed genetic analysis of the chromosome 6 locus. We created a panel of overlapping and reciprocal subcongenic lines from the B6.CAST Ldlr À/À chromosome 6 congenic strain (CON6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 58 publications
2
28
1
Order By: Relevance
“…In previous studies, we reported that 5-LO deficiency dramatically decreases aortic lesion development in two mouse models [3,4] and that humans carrying certain ALOX5 gene variants have increased carotid intima-media thickness [5]. Moreover, recent studies in humans and mice have demonstrated that various pharmacological modifiers of the 5-LO pathway decrease inflammatory biomarkers and aortic lesion formation, respectively [9,13,37], raising the possibility of developing 5-LO pathway inhibitors for the treatment of CVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we reported that 5-LO deficiency dramatically decreases aortic lesion development in two mouse models [3,4] and that humans carrying certain ALOX5 gene variants have increased carotid intima-media thickness [5]. Moreover, recent studies in humans and mice have demonstrated that various pharmacological modifiers of the 5-LO pathway decrease inflammatory biomarkers and aortic lesion formation, respectively [9,13,37], raising the possibility of developing 5-LO pathway inhibitors for the treatment of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, multiple lines of evidence support this concept, including biochemical, genetic and pharmacological studies in both mice and humans [2]. For example, we demonstrated that deficiency of the gene encoding 5-lipoxygenase (Alox5) in mice protects against the development of aortic lesions [3,4], and that promoter variants of the human ALOX5 gene are associated with increased carotid intima-media thickness [5]. Other groups have also reported findings that support the involvement of the 5-LO/LT pathway in CVD traits [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 86%
“…After 4 weeks, the heart tissue was collected as described (8). Methods for determining arterial calcification, aortic aneurysms, and atherosclerotic lesions, were described (35,36). For further information, see SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…These animals that did not survive well on the atherosclerotic diet given with only heterozygote 5-LO Ϯ mice surviving (1181). Mice in that study appeared to have been derived from congenic strain that had potentially many other differences in genes immediately surrounding 5-LO (611,1180). A relatively specific inhibitor of 5-LO was recently reported to reduce atherosclerosis in LDLR-null by 43% (315).…”
Section: Sphingolipid and Eicosanoid Signaling In Macrophagesmentioning
confidence: 99%